Pre-operative localization of solitary pulmonary nodules with computed tomography-guided hook wire: report of 181 patients. Issue 1 (December 2016) - Hanauer, Matthieu; Perentes, Jean; Krueger, Thorsten; Ris, Hans-Beat; Bize, Pierre; Schmidt, Sabine; Gonzalez, Michel
Abstract Background Video-assisted thoracic surgery (VATS) is currently performed to diagnose and treat solitary pulmonary nodules (SPN). However, the intra-operative identification of deep nodules can be challenging with VATS as the lung is difficult to palpate. The aim of the study was to report the utility and the results of pre-operative computed tomography (CT)-guided hook wire localization of SPN. Methods All records of the patients undergoing CT-guided hook wire localization prior to VATS resection for SPN between 2002 and 2013 were reviewed. The efficacy in localizing the nodule, hook wire complications, necessity to convert VATS to thoracotomy and the histology of SPN are reported. Results One hundred eighty-one patients (90 females, mean age 63 y, range 28–82 y) underwent 187 pulmonary resections after CT-guided hook wire localization. The mean SPN diameter was 10.3 mm (range: 4–29 mm). The mean distance of the lesion from the pleural surface was 11.6 mm (range: 0–45 mm). The mean time interval from hook wire insertion to VATS resection was 224 min (range 54–622 min). Hook wire complications included pneumothorax requiring chest tube drainage in 4 patients (2.1 %) and mild parenchymal haemorrhage in 11 (5.9 %) patients. Migration of the hook wire occured in 7 patients (3.7 %) although it did not affect the success of VATS resection (nodule location guided by the lung puncture site). Three patients underwent additional wedge resection by VATS during the same procedure because no lesion was identified in the surgical specimen. Conversion thoracotomy was required in 13 patients (7 %) for centrally localized lesions (6 patients) and pleural adhesions (7 patients). The mean operative time was 60 min (range 18–135 min). Pathological examination revealed a malignant lesion in 107 patients (59 %). The diagnostic yield was 98.3 %. Conclusion VATS resection for SPN after CT-guided hook wire localization for SPN is safe and allows for proper diagnosis with a low thoracotomy conversion rate.